Death and meaning: the case of Tristan - L. Peeters (Literator, 1991)
The earliest versions of the legend of Tristan have reached us in fragmentary state only, the reader therefore has to reconstruct the story and become actively involved in its interpretation. This interpretation must follow the steps taken by medieval hermeneutics which was the context in which the poets wrote and constituted the horizon of expectation and reception. A story was considered to be an integumentum, a construct in which a deeper meaning was embedded and which the reader had to reconstruct by following the verbal concatenations inside the text. In the case of Thomas’s text the verbal concatenations show that the love between Tristan and Isolde was an effort to identify totally between the lovers which is denied to them in so far as they do not die together. The reader is then left to draw his own conclusions. It seems that both Thomas and Gottfried von Strasburg want to point out the danger which lies in an exclusive passion, in a fascination which locks human consciousness up in desire and self-reflection.